P532Endocardial pacing is less arrhythmogenic than conventional epicardial pacing when pacing in proximity to scar in patients with ischemic heart failure. (18th June 2020) - Mendonca Costa, C; Neic, A; Gillette, K; Porter, B; Gould, J; Sidhu, B; Chen, Z; Elliott, M; Mehta, V; Plank, G; Rinaldi, C A; Bishop, M J; et al.
Abstract: Funding Acknowledgements: WT 203148/Z/16/Z; MR/N011007/1; RE/08/003; PG/15/91/31812; PG/16/81/32441 Background: Endocardial pacing has been shown to improve response to cardiac resynchronization therapy (CRT) in comparison to conventional epicardial pacing and the physiological activation, endocardium to epicardium, is proposed to make it less arrhythmogenic. However, the relative arrhythmic risk of endocardial and epicardial pacing has not been systematically investigated. Pacing in proximity to scar increases susceptibility to arrhythmogenesis during epicardial pacing. Whether this is also the case during endocardial pacing is currently unknown. Purpose: We investigate 1) whether endocardial pacing is less arrhythmogenic than epicardial pacing, 2) whether pacing location relative to scar plays a role in arrhythmogenesis during endocardial pacing, and 3) whether these findings could be explained by the direction of the transmural action potential duration (APD) gradient. Methods: We used computational models of ischemic heart failure and patient-specific (n = 24) left ventricular anatomy and scar morphology to simulate repolarization during endocardial and epicardial pacing. Pacing locations were selected 0.2-3.5cm from a scar. We ran simulations with a 20ms transmural APD gradient, as found in heart failure, from the epicardium to endocardium (physiological) and with this gradient inverted. We computed the volume of high (>3ms/mm) repolarization gradients (HRG) within 1cm around a scar, as a surrogate for arrhythmia risk, and analysed these with ANOVA and Tukey-Kramer post-hoc tests. Results: Simulations with a physiological APD gradient predict that endocardial pacing creates a smaller (34%) volume of HRG around (1cm) a scar compared to epicardial pacing when pacing 0.2cm from scar (Figure 1-A). The volume of HRG decreases (P < 0.05) with distance from scar for epicardial pacing but not endocardial pacing (Figure 1-A). Inverting the transmural APD gradient, inverts the trend observed with a physiological gradient. In this case, the volume of HRG is unaffected by pacing location during epicardial pacing, whereas it decreases (19%) with the distance from scar for endocardial pacing. This is illustrated in the regions highlighted in yellow in Figure 1 for endocardial pacing at 0.2 and 3.5cm from a scar with a physiological (B) and an inverted (C) gradient. Conclusions: Endocardial pacing is less arrhythmogenic (purpose 1) than conventional epicardial pacing when pacing in proximity to scar and is also less susceptible to pacing location relative to scar (purpose 2). The direction of the transmural APD gradient offers a mechanistic explanation for reduced susceptibility to arrhythmogenesis during endocardial pacing compared to epicardial pacing (purpose 3). Endocardial pacing is an attractive alternative to conventional epicardial pacing in patients with scar, as it allows pacing in proximity to scar while avoiding increasing arrhythmogenic risk in patients with ischemic heart failure.